2002
DOI: 10.1159/000063701
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Platelet Agent, Ticlopidine, Upregulates Interleukin-1-Beta-Stimulated Nitric Oxide Production in Cultured Rat Vascular Smooth Muscle Cells

Abstract: Background: Hemodialysis patients who had been treated with anti-platelet aggregation drugs, including ticlopidine, sometimes developed hypotension. The mechanism by which ticlopidine lowers the blood pressure in hemodialysis patients is unclear. To elucidate the mechanism of the action of this drug, we investigated cytokine-stimulated nitric oxide (NO) metabolism by ticlopidine in cultured rat vascular smooth muscle cells (VSMC). Methods: Nitrite, a stable metabolite of NO, and intracellular cAMP and cGMP con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…reported an immediate and direct endothelial action of thienopyridines in the isolated guinea‐pig heart, independent of antiplatelet activity [20] . Also, it has been suggested that ticlopidine enhances the interleukin 1 β ‐stimulated nitric oxide release in cultured rat smooth muscle cells via cAMP‐ and protein kinase A‐dependent mechanisms [35,36] . In cultured endothelium, thienopyridines also directly stimulated the release of PGI 2 [37] .…”
Section: Discussionmentioning
confidence: 99%
“…reported an immediate and direct endothelial action of thienopyridines in the isolated guinea‐pig heart, independent of antiplatelet activity [20] . Also, it has been suggested that ticlopidine enhances the interleukin 1 β ‐stimulated nitric oxide release in cultured rat smooth muscle cells via cAMP‐ and protein kinase A‐dependent mechanisms [35,36] . In cultured endothelium, thienopyridines also directly stimulated the release of PGI 2 [37] .…”
Section: Discussionmentioning
confidence: 99%
“…The effects induced by clopidogrel were not affected by the presence of 50 µM ADP or 0.1 µM 2-MethioADP; as for ticlopidine, no inhibition between adenine nucleotides and clopidogrel on the VSMC proliferation was evidenced. It has been shown that clopidogrel significantly inhibits intimal proliferation after arterial injury in rabbit by unknown mechanisms ( 1 ) and it has been suggested that ticlopidine enhances the interleukin 1β-stimulated NO release in cultured rat smooth muscle cells via cAMP- and pKA-dependent mechanism ( 2 ). Our experimental data indicate that thienopyridines, without hepatic biotrasformation, can directly influence vascular cell growth in culture, since both ticlopidine and clopidogrel at micromolar concentrations inhibit VSMC proliferation, whereas at higher concentrations stimulate it.…”
Section: Communicationsmentioning
confidence: 99%